Installation and First Evaluation of the King Edward Point Geodetic Observatory, South Georgia - TEFERLE, Felix Norman; White, Seth Warren; Foden, Peter R.; Strachan, Rod; Whittamore, Leslie P.; Woodworth, Philip L.; Williams, Simon D. P.; HUNEGNAW, Addisu; AHMED, Furqan (2013)
During February 2013 the King Edward Point (KEP) Geodetic Observatory was established in South Georgia through a University of Luxembourg funded research project in collaboration with the National Oceanography Centre and the British Antarctic Survey. Due to its remote location in the South Atlantic Ocean as well as being one of few subaerial exposures of the Scotia plate, South Georgia has been a key location for a number of global monitoring networks, e.g. seismic, magnetic and oceanic. However, no geodetic monitoring station had been established previously despite the global network of Global Navigation Satellite System (GNSS) stations is lacking observations from this region. In this presentation we will present a first evaluation of the observations from the KEP Geodetic Observatory for the period from 14 February to 14 April 2013. We calculate multipath characteristics and positioning statistics from precise point positioning (PPP) and discuss the installation in terms of benefits for studies of tectonics and glacio-isostatic adjustment processes. The meteorological data is evaluated by comparison to the data from the existing KEP meteorological station and a widely used numerical weather model. F1R-ING-PUL-12GSCG > GSCG > 01/04/2012 - 31/03/2015 > TEFERLE Felix Norman